Sediment Accumulation Rate in Sayung Coast, Demak, Central Java Using Unsupported 210Pb Isotope - W.A. Gemilang; U. J. Wisha; T. Solihuddin; A. Arman; K. Ondara (PPIKSN-BATAN, 2020)
Some efforts have been done to cope with coastal erosion and rob in Sayung Coast including mangrove plantation, hybrid engineering (HE), and hard structure protection. However, those efforts are not considered to be the best solution in reducing the impacts of the hazards. This study aimed to determine the sediment accumulation rates based on natural isotopes 210Pb dating and hydro-oceanographic modeling technique. According to 210Pb analysis, we calculated the sediment accumulation rates at Surodadi and Timbulsloko of 0.145 cm/year and 0.06 cm/year, respectively. The sediment compositions are dominated by terrestrial sediment typified by clay deposits. The sedimentary rate average of Sayung Coast prior to HE installation (2011-2013) was 0.195 cm/year. The rate of sediment accumulation rose to around 0.4 cm/year in 2016 in accordance with the increase of Mangrove area from around 409 hectares in 2013 to about 455.79 hectares in 2015. The increase of sedimentary rate recent years became an evidence that mitigation efforts to reduce abrasion temporarily succeeded.